Can bicarbonate replace phosphate to improve the sustainability of bioelectrochemical systems for H2 production?1. Issue 34 (15th April 2015) - Liang, Dawei; Xu, Weiwei; Liu, Yanyan; Peng, Sikan; Xie, Beizhen; Lu, Shanfu; Xiang, Yan; Liu, Hong
<x xml:space="preserve">Abstract</x> Large (80%) replacement of PO43− with HCO3− is feasible to maintain the current density and improve the sustainability of MEC.